Towards independence: a BCI telepresence robot for people with severe motor disabilities - Leeb, Robert; Tonin, Luca; Rohm, Martin; Desideri, Lorenzo; Carlson, Tom; Millán, José del R. (Proceedings of the IEEE, 2015)
This paper presents an important step forward towards increasing the independence of people with severe motor disabilities, by using brain-computer interfaces to harness the power of the Internet of Things. We analyze the stability of brain signals as end-users with motor disabilities progress from performing simple standard on-screen training tasks to interacting with real devices in the real world. Furthermore, we demonstrate how the concept of shared control-which interprets the user's commands in context-empowers users to perform rather complex tasks without a high workload. We present the results of nine end-users with motor disabilities who were able to complete navigation tasks with a telepresence robot successfully in a remote environment (in some cases in a different country) that they had never previously visited. Moreover, these end-users achieved similar levels of performance to a control group of 10 healthy users who were already familiar with the environment.
Date of current version: May 29, 2015
Gesehen am 15.06.2020